2018
DOI: 10.1002/jbm.a.36382
|View full text |Cite
|
Sign up to set email alerts
|

Effects of substrate stiffness on dental pulp stromal cells in culture

Abstract: Dental pulp stromal cells (DPSCs) can be differentiated down lineages known to either express bone or dentin specific protein markers. Since the differentiation of cells can be heavily influenced by their environment, it may be possible to influence the osteogenic/odontogenic potential of DPSCs by modulating the mechanical properties of substrate on which they are grown. In this study, human DPSCs were grown with and without hydroxyapatite (HA) microparticles on a range of substrates including fibronectin-coat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 33 publications
(80 reference statements)
2
21
0
Order By: Relevance
“…In that way, to more efficiently direct dental papilla cell fate, manipulation of the microenvironmental stiffness could offer us an exciting new tool . In recent years, several reports showed a tendency that the dental pulp cells had the odontogenic differentiation potential on the stiffer substrates both in vivo and in vitro. However, DPCs, another kind of important seed cells for tissue engineering, have rarely been reported with respect to the influence of different stiffness on their differentiation in accordance with our research. Furthermore, it is rarely known that the mechanism including mechanosensing and mechanotransduction relates with the effect of substrate stiffness on odontogenic differentiation in cells from dental tissue.…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…In that way, to more efficiently direct dental papilla cell fate, manipulation of the microenvironmental stiffness could offer us an exciting new tool . In recent years, several reports showed a tendency that the dental pulp cells had the odontogenic differentiation potential on the stiffer substrates both in vivo and in vitro. However, DPCs, another kind of important seed cells for tissue engineering, have rarely been reported with respect to the influence of different stiffness on their differentiation in accordance with our research. Furthermore, it is rarely known that the mechanism including mechanosensing and mechanotransduction relates with the effect of substrate stiffness on odontogenic differentiation in cells from dental tissue.…”
Section: Introductionsupporting
confidence: 89%
“…For example, Qu et al revealed that the scaffold is used in subcutaneous implantation with the high-stiffness-facilitated dental pulp stem cell differentiation to form the mineralized tissue, compared with the soft pulplike tissue formation on the scaffold with the low stiffness . Furthermore, Williams et al reported that dental pulp stromal cells only showed significant mineralization on very stiff (>75 kPa) substrates by testing alkaline phosphatase (ALP) activity, osteopontin (OPN) production, and mineralization . Protein marker expression related to osteogenic/odontogenic differentiation was also reported to significantly increase as the substrate stiffness increased, including alkaline phosphatase (ALP), osteocalcin, osteopontin (OPN), runt-related transcription factor-2 (RUNX-2), bone morphogenetic protein-2, dentin sialophosphoprotein, and dental matrix protein 1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there was no significant difference in the expression of RUNX-2, BMP-2, and COL1A1 between intermediate and soft groups as shown in 4 of 10 bar graphs (Figure 5), which indicated that rMSSCderived stem cells could potentially respond strongly to the stiff and soft substrates than to intermediate matrix in terms of osteogenic differentiation. Similarly, previous work by Datko's group has suggested that DPSCs may only show distinct osteogenic differentiation on very stiff substrates (>75 kPa) [54]. Although most studies concluded that an increased stiffness is conducive to osteogenic differentiation, a study, manufacturing wide range of elastic modulus, reported that softer substrates were more conducive to osteogenic differentiation as compared to the stiffer ones [55].…”
Section: Discussionmentioning
confidence: 78%
“…The advent of 3D printing and fabric weaving also supports the evolution of the structure and properties of new biomaterials . Recent research demonstrates that soft materials promote chondrogenic differentiation of stem cells while stiff materials lead to differentiation down the osteogenic lineage . Therefore the material must be initially soft to produce an environment for chondrogenesis during the early developmental phase.…”
Section: Hydrogel Scaffold For Regenerative Medicinementioning
confidence: 99%